Pengaruh Resusitasi Cairan terhadap Nilai Revised Trauma Score (RTS) pada Pasien Trauma di Instalasi Gawat Darurat RSUD dr. H. Moch. Ansari Saleh Kota Banjarmasin - Durratun Nafisah; Hanura Aprilia; Mira Mira; Noor Khalilati (MAN 4 Kota Pekanbaru, 2026)
Trauma is one of the leading causes of death and disability worldwide, accounting for approximately 50% of all deaths. Generally, trauma patients experience both external bleeding, which is visible, and internal bleeding, which is not visible; both result in the loss or reduction of blood volume. Fluid resuscitation is the primary treatment for trauma to maintain and restore oxygenation following blood loss. This study aims to analyze the effect of fluid resuscitation on the Revised Trauma Score (RTS) in trauma patients at the emergency department of Dr. H. Moch Ansari Saleh Regional General Hospital in Banjarmasin. The study employed a pre-experimental design with a one-group pretest-posttest design involving 14 participants selected via accidental sampling. Using the nonparametric Wilcoxon test, the results showed a change in the RTS score with a p-value (0.001) < α (0.005). This indicates that fluid resuscitation has an effect on increasing the RTS score in trauma patients. Rapid and appropriate fluid resuscitation plays a crucial role in supporting the initial stabilization process and improving the clinical condition of trauma patients.